Assessing the quality and value of psychological health care in civilian health plans : lessons and implications for the Military Health System - Martsolf, Grant (Research report (Rand Corporation), 2015)
"The Military Health System (MHS) strives to provide high-quality care and improve outcomes for individuals with psychological health conditions. Over the last decade, the MHS has provided care to a growing number of individuals with psychological health conditions, such as post-traumatic stress disorder (PTSD) and major depressive disorder (MDD). However, little is known about the extent to which the MHS delivers care that is consistent with evidence-based clinical practice guidelines or if it is achieving positive outcomes for its service members. To better understand these issues, the Defense Centers of Excellence for Psychological Health and Traumatic Brain Injury (DCoE) asked the RAND Corporation to describe civilian health plans' approaches to systematically measuring the quality of psychological health care delivered by providers in their networks. This work was part of a larger effort by RAND to develop a framework and identify a set of measures for monitoring the quality of care provided by the MHS for psychological health conditions"--Publisher's web site